Analisis Pemanfaatan Aset Tanah Melalui Mekanisme Sewa Sebagai Upaya Meningkatkan PAD Pada BKAD Kabupaten Manggarai - Novrianto Aleksandro Mose; I Komang Arthana; Muhammad A. H. Mushlih (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the utilization of land assets through leasing mechanisms as an effort to increase Regional Original Revenue (PAD) at the Finance and Regional Assets Agency (BKAD) of Manggarai Regency. Using a qualitative descriptive approach with case study design, data were collected through observation, in-depth interviews, and documentation involving key informants from BKAD and third-party land lessees. The study focuses on four stages: planning, implementation, supervision, and reporting. Results indicate that land asset utilization through leasing has contributed positively to PAD, although implementation remains suboptimal due to incomplete asset legality, limited asset management information systems, insufficient routine monitoring, and the absence of a comprehensive management strategy. The planning stage shows annual inventorying through SIMDA BMD, with rental values determined under Regional Regulation No. 6 of 2024. Implementation complies with Permendagri No. 7 of 2024, involving the Regent, Regional Secretariat, and BKAD. Supervision involves both internal (Inspectorate) and external (BPK) oversight. Reporting is conducted periodically and reflects real field conditions. Optimization of land asset management requires better asset inventory, acceleration of land certification, strengthened supervision, adoption of digital reporting systems, and strategic utilization of idle land to support regional fiscal independence.